Improving Career Satisfaction through Reducing Work-Family Conflict among Nurses: Career Calling as Moderator - Robiansyah, Robiansyah; Raharjo, Sugeng; Ramadhani, Melda Aulia; Abdullah, Mohd Zulkifli (Jurnal Aplikasi Manajemen, 2024)
Career calling is essential in individual career development, especially for women, such as nurses, who are prone to potential work and family conflicts. They are faced with tough challenges in order to enjoy satisfaction in their careers. This study explores the role of career calling as a moderator in the relationship between work-family conflict and career satisfaction. This study focuses on 120 nurses as respondents spread across three cities and regencies in East Kalimantan. This number of samples was obtained with a purposive approach, five times the number of indicators. The results with SEM-PLS show that work-family conflict negatively affects career satisfaction, while career calling positively affects career satisfaction. Moderation effect testing shows that career calling significantly amplifies the effect of work-family conflict on career satisfaction. Managers in health agencies must minimize the work-family conflicts of their nurses and develop a sense of calling in a nursing career to increase career satisfaction. Implication of the result: The HR function needs to manage conflict between work and family wisely and evolve people to be more inclusive with their calling in the job.